Application of stochastic model in estimation of stock return rates in capital market investments - Amadi*, I.U.; Okpoye†, O.T. (International Journal of Mathematical Analysis and Modelling, 2023)
The rigidity of financial assets lies on capital investments which geared towards bringing returns to the investors. Therefore, this paper studied the problem of system of Stochastic Differential Equations (SDE) of time-varying investments of Dangote cement PLC where multiplicative inverse effects, additive effects, additive inverse effects and multiplicative effects were used as key parameter in the model to obtain stock rate of returns. The problem was solved analytical by adopting Ito’s theorem which gave four different investment solutions. In addition, the validity of analytical solutions was clearly confirmed graphically and discussed consequently.